Pengaruh Kualitas Pelayanan, Lokasi, Dan Fasilitas Terhadap Kepuasan Konsumen Pada Klinik Pratama Suma Medika Pasar Kamis Kabupaten Tangerang Banten - Jaffar Sidik, Adjuardi; Yusuf, Ade (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of service quality, location, and facilities, both partially and simultaneously on consumer satisfaction at the Pratama Suma Medika Clinic, Pasar Kamis, Tangerang Regency, Banten. The method used is quantitative, the sampling technique uses the Slovin formula with a sample size of 100 respondents. Data analysis techniques using validity tests, reliability, classical assumption tests, simple linear regression analysis, multiple linear regression, correlation coefficients, determination coefficients, t-test hypothesis tests, and f-tests. The results of this study indicate that partially the results of the simple linear regression test of service quality on consumer satisfaction obtained the regression equation Y = 17.135 + 0.606X1 and service quality has a significant positive effect on consumer satisfaction. This can be proven by t count> t table (7.456> 1.984). The results of simple linear regression of location on consumer satisfaction obtained the regression equation Y = 21.528 + 0.498X2, Location has a significant positive effect on Consumer Satisfaction can be proven that t count> t table (6.479 > 1.984). The results of simple linear regression of facilities on consumer satisfaction obtained the regression equation Y = 9.727 + 0.769X3, Facilities have a significant positive effect on Consumer Satisfaction can be proven that t count> t table (6.479 > 1.984), from Simultaneously Service Quality, Location, and Facilities have a significant effect on Consumer Satisfaction with the regression equation Y = 6.125 + 0.148X1 + 0.114X2 + 0.596X3, And the results of the hypothesis test obtained the value of f count> f table (47.170 > 2.699)..